História da expansão do ensino superior em Goiás e a gênese do curso de Administração de Empresas em Quirinópolis, 1990–2005 - Costa, Gercimar Martins Cabral (2022)
The objective of the dissertation is to reflect on the process of expansion of Higher Education of Administration in Brazil and the internalization of the Course in the Southwest of the State of Goiás in the period of 1990-2005, a period that comprises profound transformations in the political, economic and social spheres of the parents. This work is linked to the line of research in History and Historiography of Education and aims to analyze the context of the origin and internalization of the teaching of Business Administration in the country. The methodological course is a historical-educational research relevant to the history of educational institutions, of a documentary nature, which seeks to highlight the importance of the Business Administration Course and build a historical understanding of the diffusion of higher education in Goiás with a focus on the XXI century. The researched universe includes the expansion and interiorization of colleges in the city of Quirinópolis, especially the analysis of Faculdade Quirinópolis, as the first private college based in the city of Quirinópolis, in the southwest of the State of Goiás. The methodological process was structured with the perspective of understanding the historical conjuncture of higher education in Brazil, the expansion and interiorization of higher education, as a basis, it was used theoretical references contained in books, articles, laws, decrees, websites and documents of the institution. research object. The research results show the expansion of the Business Administration course, highlighting the local demand for the Course in its seventeen years of offer in that Institution (started in 2005). It is concluded that the expansion and internalization of higher education allows for greater integration, especially for young people leaving high school and entering graduation.